Neovaginal Prolapse in Male-to-Female Transsexuals: An 18-Year-Long Experience. (7th May 2014) - Bucci, Stefano; Mazzon, Giorgio; Liguori, Giovanni; Napoli, Renata; Pavan, Nicola; Bormioli, Susanna; Ollandini, Giangiacomo; De Concilio, Bernardino; Trombetta, Carlo
Abstract : Neovaginal prolapse is a rare and distressing complication after male-to-female sexual reassignment surgery. We retrospectively analysed the prevalence of partial and total neo-vaginal prolapses after sexual reassignment surgery in our institute. During the years, two different techniques have been adopted with the aim of fixing the neovaginal cylinder. In the first, two absorbable sutures are placed at the top of the penoscrotal cylinder and fixed to the Denonvilliers fascia. In the second, two additional sutures are added from the posterior/midpoint of the flap to the prerectal fascia. We enrolled 282 consecutive transsexual patients. 65 (23.04%) out of the 282 were treated with the first technique and the following 217 (76.96%) with the last technique. In the first technique, 1 case (1.53%) of total prolapse and 7 cases (10.76%) of partial prolapse were observed, while in the other 217 patients treated with the second technique only 9 cases of partial prolapse were observed (4.14%) and no cases of total prolapse. All prolapses occurred within 6 months from the procedure. In our experience, the use of 4 stitches and a more proximal positioning of the sutures to fix the penoscrotal apex with the Denonvilliers fascia guarantees a lower risk of prolapse.